Penerapan dan Analisis Phylosophical Theory Patricia Banner “Novice To Expert” pada Asuhan Keperawatan Chf - Humairah, Faradila; Nursanti, Irna (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Congestive Heart Failure (CHF) is the inability of the heart to maintain adequate cardiac output to meet metabolic and oxygen needs in the tissues despite adequate venous return, with signs and symptoms of shortness of breath and fatigue caused by abnormalities in the function of the heart structure. Patricia Benner's theory explains that practitioner knowledge produces new ideas in scientific disciplines. By using appropriate operational and theoretical terms to define the concepts in the theory. The theory developed by Patricia Benner has 5 levels "Novice, Advanced Beginner, Competen, Proficience, Expert" which describes the main levels of experience for each practitioner. Objective: to find out the application of Patricia Benner's theoretical concepts in nursing care. Method: nursing process approach using Patricia Benner's nursing theory model, data collection technique namely case study. Results: The Benner model places nurses according to their level of expertise from Novice nurses who carry out assessments and formulate diagnoses through the guidance of Advanced Begginer nurses. Begginer intervenes according to the level of dependency. Results and implementation criteria are determined by Competent nurses, the success of the intervention according to the evaluation is carried out by Proficient nurses. As a consultation for nurses and families, it is carried out by expert nurses. Conclusion: Achieving success in nursing care, especially for patients with CHF, can be determined by the level of expertise of the nurse providing care.